2016
DOI: 10.1002/fld.4222
|View full text |Cite
|
Sign up to set email alerts
|

Advanced numerical method for a thermally induced slug flow: application to a capillary closed loop pulsating heat pipe

Abstract: Summary An advanced hybrid lumped parameter code for the simulation of Pulsating Heat Pipes is developed. Being able to simulate transient operative conditions and removing common physical simplified assumptions, it represents a step forward with respect to the present models of passive two‐phase systems. Mass, momentum and energy balances account for the thermal and fluid‐dynamics phenomena. Heterogeneous and homogeneous phase changes are directly integrated. In addition, a fitting correlation for the wall/va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Furthermore, the microgravity tests in horizontal position confirmed a previous numerical analysis [17], suggesting that the PHP performance in zero gravity condition was not different from the horizontal operation on ground in case of planar geometries. Later on, Manzoni et al [18] proposed an advanced lumped numerical code and the predicted results showed a very good agreement with the experimental thermo-physical behavior during the gravity field transition obtained in [16]. Another test of a PHP in microgravity conditions was performed by Taft et al [19] ) are milled and the device is partially filled up with acetone.…”
mentioning
confidence: 72%
“…Furthermore, the microgravity tests in horizontal position confirmed a previous numerical analysis [17], suggesting that the PHP performance in zero gravity condition was not different from the horizontal operation on ground in case of planar geometries. Later on, Manzoni et al [18] proposed an advanced lumped numerical code and the predicted results showed a very good agreement with the experimental thermo-physical behavior during the gravity field transition obtained in [16]. Another test of a PHP in microgravity conditions was performed by Taft et al [19] ) are milled and the device is partially filled up with acetone.…”
mentioning
confidence: 72%
“…However, if the control volume is adiabatic, it cannot be assumed that the phase changes are both isothermal and isobaric, thus only the assumption of has been maintained (assumption 7). As shown in [30], evaporated and condensed mass, , as well as the final length of the vapor elements,…”
Section: Heterogeneous Phase Changesmentioning
confidence: 97%
“…are computed. For more details one should refer to the annex A reported in [30]. Note that the 1 st Adams-Bashforth integration scheme [31] has been adopted to integrate mass and energy balances if not differently indicated.…”
Section: Phase Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsating heat pipes (PHPs) are becoming a popular technology to address passive thermal management of nuclear, defence and space applications [5][6][7]. The PHP design variants proposed and studied to date, have the potential to meet many of the present and future specific requirements from electronics cooling [8,10], heat recovery [2,15] and passive cooling of reactor containments, to name a few.…”
Section: Introductionmentioning
confidence: 99%